Evaluasi Efektivitas Konseling Kehamilan dalam Meningkatkan Pengetahuan dan Perilaku Ibu Hamil di Puskesmas Poasia, Kendari, Sulawesi Tenggara - Suhartati Suhartati; Erniwati Daranga; Fath Irtaniyah Rahman; Arbiyah Arbiyah (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2026)
This Community Service (PKM) project aims to evaluate the effectiveness of the pregnancy counseling program in improving the knowledge and behavior of pregnant women at the Poasia Community Health Center in Kendari City, Southeast Sulawesi. The method used was an educational approach through individual and group counseling, accompanied by pre- and post-tests to measure knowledge gains and observe changes in health behaviors during pregnancy. Results showed significant improvements in understanding pregnancy danger signs, adherence to antenatal visits, consumption of iron supplements, and healthy lifestyle practices. This program demonstrates that structured and ongoing counseling is effective in supporting improvements in the quality of pregnant women's health at the primary care level.